Gen Z’s Perceptions of Masculinity and Violence in the Series “Weak Hero Class 2” - Elmira Zachra Putri Hamidun (International Journal Labs, 2026)
The development of digital platforms has made it easier for audiences to access and watch Korean drama series, including the series “Weak Hero Class 2.” This study aims to understand how Indonesian Gen Z responds to and interprets the portrayal of masculinity and violence in the series, as well as to explore their perspectives. The method used was descriptive qualitative, and data analysis was conducted through reception analysis based on Stuart Hall's theory. The results show that audiences interpret representations of masculinity and violence in various ways. The decoding process and audience interpretation reveal both positive and negative views of the depiction of violence, which is not straightforward. The presence of both acceptance and rejection among Gen Z viewers presents a paradox. Violence is viewed as part of social dynamics, and, on an individual level, masculinity is closely linked to violence, specifically physical aggression. Three types of meaning dominant-hegemonic, negotiated, and oppositional emerge in how audiences receive representations of masculinity and violence in “Weak Hero Class 2.” Audience background influences interpretation and affects how they accept or reject the portrayals of masculinity and violence in the series.